Detection of intermediates in dual gold catalysis using high-resolution ion mobility mass spectrometry - Greisch, Jean-François; Bay, Sarah; Wurm, Thomas; Rudolph, Matthias; Schulmeister, Jürgen; Hashmi, A. Stephen K. (Organometallics, 2018)
We have probed for reaction intermediates involved in the dual-gold-catalyzed activation of a conjugated 1,5-diyne substrate and its further coupling to benzene in the liquid phase. This was done by sampling the reaction mixture by electrospray ionization followed by high-resolution ion mobility mass spectrometry—under conditions allowing for the resolution of structural isomers differing in their collision cross sections by less than 0.5%. For the cationic mass corresponding to catalyst + diyne (activation stage) we resolve four isomers. At the mass corresponding to catalyst + diyne + benzene, two isomers are observed. By comparing the experimentally obtained cross sections to those inferred for model structures derived from density functional computations, we find our measurements to be consistent with the proposed solution mechanism. This constitutes the first direct observation of intermediates in dual gold catalysis and supports the previous inference that the mechanism involves cooperative interactions between two gold centers.